Yesus Kristus Anak Domba yang Sempurna: Finalitas Penebusan Berdasarkan Yohanes 1:29 - Ibrahim Ibrahim; Fonny Natalia Joseph; Sri Wahyuni (Sekolah Tinggi Teologi Sangkakala Jakarta, 2026)
Abstract This study discusses the theological meaning of John the Baptist's statement in John 1:29 about Jesus as the Lamb of God who takes away the sins of the world. This study is carried out because the concept is often understood in a limited way, even though it has important significance in redemptive theology. This research aims to examine the theological meaning of the concept of the Lamb of God and show the finality of Christ's redemptive work. This study uses a qualitative approach with the method of biblical exegesis through the analysis of Greek texts, tracing the background of the Old Testament, and the study of theological literature. The results of the study show that the term Lamb of God refers to the fulfillment of the Passover sacrifice and the sin offering in the Old Testament. Through His sacrifice on the cross, Christ offered the perfect and final sacrifice that effectively took away the sin of mankind with universal coverage. This study concludes that Christ's redemptive finality provides a theological basis for the certainty of salvation and renews the church's understanding of worship and mission. Key words: Lamb; Sin; finality; Redemption; Jesus Christ. Abstrak Penelitian ini membahas makna teologis pernyataan Yohanes Pembaptis dalam Yohanes 1:29 tentang Yesus sebagai Anak Domba Allah yang menghapus dosa dunia. Kajian ini dilakukan karena konsep tersebut sering dipahami secara terbatas, padahal memiliki signifikansi penting dalam teologi penebusan. Penelitian ini bertujuan untuk menelaah makna teologis konsep Anak Domba Allah serta menunjukkan finalitas karya penebusan Kristus. Penelitian ini menggunakan pendekatan kualitatif dengan metode eksegesis biblika melalui analisis teks Yunani, penelusuran latar belakang Perjanjian Lama, dan kajian literatur teologis. Hasil penelitian menunjukkan bahwa istilah Anak Domba Allah menunjuk pada penggenapan korban Paskah dan korban penghapus dosa dalam Perjanjian Lama. Melalui pengorbanan-Nya di salib, Kristus mempersembahkan korban yang sempurna dan final yang secara efektif menghapus dosa manusia dengan cakupan universal. Penelitian ini menyimpulkan bahwa finalitas penebusan Kristus memberikan dasar teologis bagi kepastian keselamatan serta memperbarui pemahaman gereja tentang ibadah dan misi. Kata kunci: Anak Domba; Dosa; finalitas; Penebusan; Yesus Kristus.